2007
DOI: 10.1177/0964663907079763
|View full text |Cite
|
Sign up to set email alerts
|

`Getting Through the List': Judgecraft and Legitimacy in the Lower Courts

Abstract: This article examines the judgecraft required when judicial officers actively manage the time pressures created by long and unpredictable case lists. It considers the implications of this time management for the legitimate exercise of judicial authority. In particular, we focus on the strategy of altering the temporal sequence of the list by standing matters down and recalling them later in the list. This strategy, especially when initiated by the judicial officer, is analysed in light of the temporal goals of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 13 publications
(23 reference statements)
1
42
1
Order By: Relevance
“…In terms of scheduling, our findings concur with Mack and Anleu's (2007) conclusion that scheduling and judicial discretionary actions are closely related and represent an embellishment of work that has highlighted that certain decisions are more likely after a break (Danziger et al, 2011) by emphasizing patterns of judicial behaviours across weekdays (as distinct to within them). The fact that the analysis suggested that helpfulness declined through the week may point to the effect that repetition, and even boredom, can have over procedural discretion (see Cowan and Hitchings, 2007).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In terms of scheduling, our findings concur with Mack and Anleu's (2007) conclusion that scheduling and judicial discretionary actions are closely related and represent an embellishment of work that has highlighted that certain decisions are more likely after a break (Danziger et al, 2011) by emphasizing patterns of judicial behaviours across weekdays (as distinct to within them). The fact that the analysis suggested that helpfulness declined through the week may point to the effect that repetition, and even boredom, can have over procedural discretion (see Cowan and Hitchings, 2007).…”
Section: Discussionsupporting
confidence: 87%
“…Most published studies of judicial behaviour rely upon (i) information from judges themselves in response to interviews, questionnaires or in formal written opinions; (ii) the judgements reached in actual cases; or (iii) experimental results (Conley and O'Barr, 1988). Observational methods, for their part, have often been seen as separate to quantitative analysis rather than as complementary to it (Mack and Anleu, 2007). Our approach fuses observational work with quantitative methodologies, offering innovative new insights.…”
mentioning
confidence: 99%
“…Gender diversity is thought to increase public confidence, to better reflect society as a whole in the judiciary, to widen access to positions Nussbaum (1996); Popovic (2002), p 129;Shaman (1996). 20 Mack and Roach Anleu (2007, 2010a, 2013. Tyler (1984Tyler ( , 2003; see also Lind and Tyler (1988).…”
Section: Judicial Rolesmentioning
confidence: 98%
“…1 All magistrates are paid; the minimum statutory qualification for appointment includes admission as a barrister/solicitor/legal practitioner. Magistrates preside over highvolume, first instance courts with a wide general jurisdiction in less serious criminal cases and lower value civil matters (Lowndes 2000;Mack and Roach Anleu 2007). Magistrates sit alone (without juries) and make many decisions, typically extemporaneously, on law and facts.…”
Section: The Australian Magistracymentioning
confidence: 99%